Pickering emulsion stabilized by gliadin/soybean polysaccharide composite colloidal nanoparticle: Physicochemical properties and its application on washing of fresh-cut cabbage. (November 2022) - Shen, Chen; Chen, Wenqing; Li, Changzhu; Chen, Xiaochen; Cui, Haiying; Lin, Lin
Graphical abstract: Highlights: The colloidal nanoparticle was prepared by various ratios of Gl and SP. Essential oil-loaded Pickering emulsion was stabilized by colloidal nanoparticle. Pickering emulsion possessed excellent antibacterial activity against E. coli O157:H7. The preferable quality of fresh-cut cabbage was obtained by Pickering emulsion. Abstract: In this study, gliadin (Gl) and soybean polysaccharide (SP) were selected and used to prepare composite colloidal nanoparticles, which were used to stabilize Pickering emulsion loaded with Eucalyptus citriodora essential oil (ECEO) for washing fresh-cut cabbage. FTIR and fluorescence spectra showed that Gl and SP were assembled to form composite colloidal nanoparticles by electrostatic adsorption, and the appropriate particle size and zeta potential were obtained when the ratio of Gl and SP was 1:1. The confocal laser scanning microscopy (CLSM) results demonstrated that the colloidal nanoparticles adsorbed and arranged at the oil–water interface and thus formed a thick interface film, leading to preferable stability of the prepared Pickering emulsion. The Pickering emulsion was further applied to the washing of fresh-cut cabbage. It was found that Pickering emulsion not only inhibited the growth of E.coli O157:H7 on the surface of fresh-cut cabbage but also maintained the chroma, chlorophyll content, and sensory quality of fresh-cut cabbage. In summary, our research work broadened the application of Pickering emulsion in the preservation of vegetables and provided a valuable reference.